A Conceptual Analysis of Utilizing English Songs in Teaching Speaking Skills - Safitri, Isnaini Amanda; Najwa, Siti (Cipta Pustaka Nusantara, 2024)
This study investigates the effectiveness of using English songs to enhance speaking skills among seventh-grade students at SMPN 26 Bandar Lampung. A quasi-experimental design was employed, with 30 students in the experimental group, who received instruction incorporating English songs, and 30 students in the control group, who were taught using traditional methods. Data were collected through pretests and posttests assessing speaking skills across five criteria: fluency, pronunciation, vocabulary usage, grammar, and confidence. Additionally, a student motivation questionnaire was administered to gauge engagement and attitudes toward learning. The results indicated that the experimental group showed significant improvement in all areas, with notable gains in fluency and confidence, compared to the control group. Students in the experimental group also reported higher motivation and enjoyment in learning English through songs. The study concludes that English songs can be a valuable tool in improving speaking skills, fostering student engagement, and reducing anxiety. However, the study also highlights the need for teacher training and addressing logistical challenges to fully integrate songs into language instruction. Future research should explore larger, more diverse samples and examine the long-term effects of song-based learning.